IL6-174G > C genetic polymorphism influences antidepressant treatment outcome. (17th February 2017) - Carvalho, Serafim; Santos, Marlene; Lima, Luís; Mota-Pereira, Jorge; Pimentel, Paulo; Maia, Dulce; Correia, Diana; Gomes, Sofia; Cruz, Agostinho; Medeiros, Rui
Abstract: Background: Major depressive disorder is a condition associated with dysregulated cytokine levels; among these, IL6. Furthermore, genetic variations within cytokine genes have been proposed to predict antidepressant treatment outcome. Objectives: This study aims to evaluate the role of IL6-174G > C and IL6R D358A A > C functional polymorphisms in antidepressant treatment phenotypes, specifically remission, relapse, and treatment resistant depression (TRD). Methods: The referred polymorphisms were genotyped in 80 MDD patients followed at Hospital Magalhães Lemos, Portugal, within a period of 27 months. Results: It was found that patients carrying IL6-174 GC genotype present a protection towards the development of TRD (OR = 0.242; 95% CI = 0.068–0.869; p  = .038), when compared with GG genotype. Additionally, carriers of IL6-174  CC genotype remit earlier than patients with IL6-174 GG/GC genotypes, with a median time to remission of 6 weeks for CC carriers and 15 weeks for GG or GC carriers ( p  = .030, Log-rank test). No association was found between IL6R D358A genetic polymorphism and any of the treatment phenotypes evaluated. Conclusions: The IL6-174G > C polymorphism influences antidepressant treatment outcome in this sub-set of MDD patients, providing a putative mechanistic link for the dysregulated IL-6 levels described in the literature in patients with TRD.